Assessing career success: the role of protean career attitude, organizational learning practices, and employability perception - Poh Kiong Tee; Devinder Kaur; Bee Lian Song; Behrooz Gharleghi (Cogent Business & Management)
The main objective of this study is to assess the career success factors by adopting a convergent view of individual and organisational career practices in an academic career context. Due to the greater emphasis on employability as an important measure for career success, the (direct and indirect) impacts of employability perception along the relationship were investigated by distinguishing between perceived internal employability with external employability. Protean career attitude has no significant direct influence on career success, according to data from 256 Malaysian academics; rather, it has an indirect effect on career success mediated by perceived internal and external employability. Whereby, organizational learning practices significantly influence career success directly and indirectly via perceived employability. Multiple mediation analyses revealed the significant mediating effects of internal and external employability perception along the relationships between a protean career attitude, organizational learning practices, and career success, with perceived external employability having higher direct and mediating effects on career success. The study’s findings are explored, as well as their limitations and future research directions.